Governing through institution building institutional theory and recent European experiments in democratic organization - Olsen, Johan P. (Oxford University Press, 2010)
'Governing Through Institution Building' offers an organization theory-based institutional approach to understanding political organization and government by examining large-scale institutional reforms.